The association between sleep dysfunction and psychosis-like experiences among college students. (February 2017) - Andorko, Nicole D.; Mittal, Vijay; Thompson, Elizabeth; Denenny, Danielle; Epstein, Gregory; Demro, Caroline; Wilson, Camille; Sun, Shuyan; Klingaman, Elizabeth A.; DeVylder, Jordan; Oh, Hans; Postolache, Teodor T.; et al.
Abstract: Sleep problems are prominent and pervasive clinical issues experienced by many people with psychotic disorders, often causing distress and functional impairment. Sleep problems are also related to psychosis-like experiences (PLE; non-diagnosable phenomenon such as transient perceptual disturbances, unusual thoughts, periodic suspiciousness) in epidemiological studies. Prior studies in this field have used brief measures that precluded the ability to test (1) whether risk for psychosis-like experiences are related to specific sub-types of sleep disturbance, and (2) whether sleep disturbance is specifically related to clinically significant (i.e., distressing) psychosis-like experiences. The current project examined the relation between specific sleep issues, and PLEs and distress associated with PLEs, in a college sample. Participants ( N =420) completed the Prodromal Questionnaire-Brief (PQ-B), which assesses PLEs and associated distress, and the Iowa Sleep Disturbances Inventory – extended version (ISDI-E), which assesses thirteen separate disturbed sleep domains. Symptoms of fragmented sleep, sleep hallucinations, and night anxiety significantly correlated with PLEs, and several sleep domains were significantly associated with PLE-related distress. Highlights: Fragmented sleep, sleep hallucinations, and night anxiety correlate with PLEs Insomnia, night anxiety, and parasomnias correlate with average PLE distress Clinicians can consider using this information to begin to disentangle typical versus clinical variations of PLE experience.